2014
DOI: 10.1103/physrevb.90.020403
|View full text |Cite
|
Sign up to set email alerts
|

Spin-liquid phase and order by disorder of classical Heisenberg spins on the swedenborgite lattice

Abstract: Frustration refers to the inability to satisfy competing interactions simultaneously, often leading to a large number of degenerate ground states. This can suppress ordering tendencies, sometimes resulting in a spin-liquid phase. An intrinsic effect lifting this degeneracy is entropic order by disorder. We present strong evidence that a classical nearest-neighbor Heisenberg model on the swedenborgite lattice exhibits both an extended spin-liquid phase as well as entropic order-by-disorder choosing coplanar con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
5
2
Order By: Relevance
“…The ground states of classical spins satisfy constraints (a "sum rule" 9,10 ), which determine their degeneracy and spin ordering. Recent numerical studies 15 showed that a large part of the phase diagram of this model is occupied by a spin-liquid state (see Fig. 1), in which the dimensionality of spin correlations depends on temperature and τ .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The ground states of classical spins satisfy constraints (a "sum rule" 9,10 ), which determine their degeneracy and spin ordering. Recent numerical studies 15 showed that a large part of the phase diagram of this model is occupied by a spin-liquid state (see Fig. 1), in which the dimensionality of spin correlations depends on temperature and τ .…”
Section: Introductionmentioning
confidence: 93%
“…The cycloidal spiral favored by the Lifshitz invariant Eq. (15) preserves the norms of V 1 and V 2 as well as their orthogonality, as it favors a simultaneous rotation of these two vectors around the axis n [V 1 × V 2 ]. The direction of the spiral wave vector, δQ s , (counted from the K-point in the reciprocal state) is left undetermined by this Lifshitz invariant of first order in gradient.…”
Section: F Symmetry Analysis Of Incommensurate Orderingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for the phase boundary are shown in Fig. S1 DlogPade [5,3] DlogPade [4,4] DlogPade [8,2] DlogPade [7,3]u DlogPade [6,4]u DlogPade [5,5] DlogPade [4,6] Dlog [5,5]u Dlog [4,6]u Dlog [8,2]u polarized phase ordered phase…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Recently, it was found that interesting effects of frustrated magnetism can also be encountered in the threedimensional swedenborgite systems. For example, classical O(3) Heisenberg spins on this lattice exhibit a wide spin liquid regime for a certain parameter and temperature range and can undergo a fluctuation driven order by disorder transition to a nematic phase at very low temperatures [7]. It was also shown that the classical Ising model with and without longitudinal magnetic field boasts different phases with extensive and subextensive ground-state degeneracy [8].…”
mentioning
confidence: 98%